2011
DOI: 10.1093/ajae/aar026
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does the Supplemental Nutrition Assistance Program Reduce Food Insecurity?

Abstract: Nearly 15% of all U.S. households and 40% of near-poor households were food insecure in 2009. The Supplemental Nutrition Assistance Program (SNAP) is the cornerstone of federal food assistance programs and serves as the first line of defense against food-related hardship. This paper measures the effectiveness of SNAP in reducing food insecurity using an instrumental variables approach to control for selection. Our results suggest that receipt of SNAP benefits reduces the likelihood of being food insecure by ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
219
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(241 citation statements)
references
References 29 publications
(50 reference statements)
9
219
2
2
Order By: Relevance
“…36--- 40 We did not examine the relationship between participation in food assistance programs here because these models do not account for self-selection into the programs. Households that are having more difficulty meeting their food needs are more likely to participate in food assistance programs and more likely to be food insecure.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…36--- 40 We did not examine the relationship between participation in food assistance programs here because these models do not account for self-selection into the programs. Households that are having more difficulty meeting their food needs are more likely to participate in food assistance programs and more likely to be food insecure.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Cereales Forrajes Legumbres Hortalizas Industriales Oleaginosas que los países subdesarrollados como México, de acuerdo con lo planteado por Ratcliffe et al (2011), ya no cuentan con una política de ajuste estructural como apoyos al crédito y la comercialización para los cultivos de subsistencia como el frijol y el maíz, abandonando a las localidades rurales. Por otro lado, si bien tanto el PIB agropecuario de Sinaloa como el nacional han tenido perío-dos de estancamiento, el ritmo de crecimiento sigue al alza.…”
Section: Tubérculosunclassified
“…This finding may initially seem counterintuitive, but is in fact a natural consequence of the fact that the programme and others like it are reaching families with the greatest need. However, as noted above, carefully constructed empirical designs that take advantage of natural experiments to address selection have found that participation in SNAP and other programmes is associated with decreased food insecurity (2)(3)(4)(5)(6) . In this sense, the use of geographic accessibility as a proxy for participation is a boon, since it is far less likely that families with high levels of need (food insecurity) choose where to live because of proximity to a summer meals site.…”
Section: Addressing Selection Biasmentioning
confidence: 99%
“…In 2013, the fifteen domestic food and nutrition assistance programmes administered by the USDA reached about 25 % of Americans at a cost of nearly $US 109 billion (1) . Studies of the largest of these programmes (including the Supplemental Nutrition Assistance Program (SNAP) and the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC)) have most frequently found that they are successful in reducing both household and child food insecurity (2)(3)(4)(5)(6) . However, much less is known about how other nutrition programmes impact household food security.…”
mentioning
confidence: 99%